Development of an enzyme-linked immunosorbent assay for quantification of Salmonella enteritidis-specific antibodies in egg yolk - Tayeb,IT (2006)
The present study aims at developing an indirect ELISA to quantify yolk antibodies specific to all surface proteins of the invasive Salmonella Enteritidis (SE), which acquired the 1.8, 14.1, and ~ 50 Kb plasmids. An ELISA checkerboard was used in four different experiments to account for the different parameters included in the preliminary ELISA procedure, and consequently to maximize the difference in Optical Density (OD) values between control positive and negative yolk samples. The first experiment aimed at studying the impact of 5% Bovine Serum Albumin (BSA) dissolved in distilled water as a blocking reagent on a 28 µg/well SE antigen-coated plate, while applying the positive and negative control yolk samples to different concentrations of Phosphate-Buffered Saline (PBS).Conjugate application was maintained constant at a dilution of 1:500 in PBS. The second experiment was similar to the first one, but the positive and negative control yolk samples were diluted in PBS-Tween 20, and the conjugate dilution was changed to 1:1500 in PBS-Tween 20. In the third experiment, the conjugate was diluted at 1:1500 in 5% BSA/PBS-Tween 20 diluent or PBS-Tween 20 diluent with no 5% BSA. The objective of the fourth experiment was to study the impact of four different concentrations of SE-coated antigen levels (28µg/well, 56µg/well, 84µg/well, and 112µg/well), while fixing the blocking step with 5% BSA in distilled water, and the conjugate dilution set at 1:1000 in 5% BSA/PBSTween 20, and fixing the control yolk samples dilution at 1% in PBS-Tween 20. This last experimental procedure allowed the highest difference in mean absorbance OD values of the positive control minus the negative control samples, which was equivalent to 0.381. In addition, the final protocol for this ELISA was applied on individual egg yolk samples of two groups of chicken layers: one challenged in the esophagus at 11 days with 5.4 x 10(10) CFU/ml/bird of SE, and the second group was not challenged. The mean OD values of the egg yolk of antibodies specific against SE of the two groups were significantly different (0.8578 versus 0.5250; p<0.05), which indicates the possible application of the developed ELISA for screening SE infection by examining egg yolks produced by commercial layers.